2014
DOI: 10.4236/jct.2014.56067
|View full text |Cite
|
Sign up to set email alerts
|

Serum Caspase-3 and Caspase-7 as Predictive Factors of Response in Locally Advanced and Metastatic Breast Carcinoma

Abstract: Introduction: Breast cancer is the most common cancer in women and the second most frequent cause of cancer death. Several factors affect response to chemotherapy including nodal status, hormonal status and human epidermal growth factor receptor (Her-2). Aim of Study: The study is aiming at evaluating Caspase-3, 7 levels in serum of patients with locally advanced and metastatic breast cancer and establishing the relation between Casepase level and response to chemotherapy. Patients and Methods: The study was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The finding that serum NT-proBNP decreases in some responders to pembrolizumab requires validation with other data sets. Studies have also shown that the activation of CASP-3 is a requirement for apoptosis induction in response to chemotherapeutic drugs such as taxanes and doxorubicin (31). A study evaluated CASP-3 levels in the serum of 60 patients with locally advanced and metastatic breast cancer and found that the 10 complete responders to chemotherapy showed a 1.7-3-fold increase in serum CASP-3, 24 hours after the completion of the first cycle of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that serum NT-proBNP decreases in some responders to pembrolizumab requires validation with other data sets. Studies have also shown that the activation of CASP-3 is a requirement for apoptosis induction in response to chemotherapeutic drugs such as taxanes and doxorubicin (31). A study evaluated CASP-3 levels in the serum of 60 patients with locally advanced and metastatic breast cancer and found that the 10 complete responders to chemotherapy showed a 1.7-3-fold increase in serum CASP-3, 24 hours after the completion of the first cycle of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It maintains the integrity of mitochondria by preventing proapoptotic proteins such as Bax or Bak from initiating this pathway (Ebied et al, 2013). In breast cancer, the expression of Bcl-2 has been associated with the presence of markers of differentiation and with a longer survival in node-negative or nodepositive patients (Hammoud et al, 2014). Caspase-3 plays a key role in both the death receptor pathway, initiated by Caspase-8.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that Caspase-3 activation is required for apoptosis induction in response to chemotherapeutic drugs e.g., Taxanes, 5-fluorouracil, and doxorubicin (Bellarosa et al, 2001). However, little work has been made to evaluate levels of Caspases in serum of patients under treatment (Hammoud et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer is the leading cancer and the leading cause of cancer death in women worldwide [1] [2]. This condition was diagnosed in women at a frequency of 24.2% and was responsible for nearly 15% of deaths in 2018 [2]. This cancer is also the first diagnosed and the leading cause of cancer deaths in women in developing countries [1].…”
Section: Introductionmentioning
confidence: 99%